GENDER DYSPHORIA IN CHILDREN AND ADOLESCENTS - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2021)
Gender dysphoria (GD) is defined as an apparent incongruence between assigned sex and experienced gender. Scholars across the world are attempting to achieve guidelines for a universal approach for children and adolescents experiencing GD. Recent studies have highlighted the importance of the biopsychosocial model as a holistic template for gender dysphoria. Youth with gender dysphoria often evince emotional and behavioral problems resulting from the stress of being marginalized and being forced to inhabit a body that does not match the experienced gender. The assessment processes for young people with GD are complex: numerous crucial factors regarding gender identity and possible psychopathologies must be contemplated by a child and adolescent psychiatrist. Treatment guidelines establish different protocols of beginning treatment for different age groups

however, consensus has not yet been achieved in approaches applied to GD in discrete clinics.
Keywords: Gender dysphoria; bio-psycho-social model; TO-FEMALE TRANSSEXUALS; IDENTITY DISORDER; PSYCHIATRIC COMORBIDITY; SEX-DIFFERENCES; YOUNG-PEOPLE; TRANSGENDER; DEMOGRAPHICS; METAANALYSIS; HEALTH; CARE